(untitled) (Nigerian Journal of Technology, 2016)
Ramat Park is one of the popular Parks in Benin City which is in form of a roundabout connecting traffic from Benin City to the North and Central part of the state including Delta state. In most cases, especially on market days, there is a gridlock within the park which necessitates the uncontrolled honking of horns and emission of other vehicular noise in a bid to checkmate reckless driving. Traffic noise was measured within a period of one month using digital noise meter at 10m away from the source of the noise and about 1.2m above ground level. Two traffic models (Rahul Singh Equation and Calixto Model) were used to calculate the vehicular noise level and the values obtained correlated well with the observed values. The plots of the measured and computed noise levels gave Root Mean Squares (RMS) of 0.776 and 0.839respectively.This indicates that the pattern of the scattered plot is narrow and there is a strong relationship between both computed and measured noise. It was therefore concluded that indiscriminate and reckless activities of drivers (especially commercial bus drivers) were responsible for the noise emission while enforcement of traffic laws in the state and relocation of the motor park close to the square were recommended control measures for noise reduction. http://dx.doi.org/10.4314/njt.v35i4.4